Agarose composite hydrogel material containing microspheres and application thereof
Patent Information
- Application Number
- CN202311731260.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-15
- Publication Date
- 2024-12-27
AI Technical Summary
Agarose hydrogel materials are difficult to sterilize, especially under high temperature conditions, which will lose water and change physical properties, resulting in precipitation or melting of microspheres, making it difficult to achieve stable production and use.
Add cellulose and/or cellulose derivatives to the agarose hydrogel, maintain the stability of the gel and the suspension state of the microspheres through irradiation sterilization technology, prevent settlement and water loss, and form an irradiation-resistant hydrogel Material.
It realizes safe and sterile production of agarose hydrogel, reduces production costs, and ensures the quality stability and safety of the product. At the same time, the biocompatibility of microspheres in the body and long-term filling effect are achieved.
Smart Images

Figure CN119185647A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an agarose composite hydrogel material containing microspheres, a preparation method thereof and uses in the fields of medical cosmetology and biomedical technology. The present invention further comprises an injection containing the hydrogel material. Background Art
[0002] Injection beauty is a type of non-surgical plastic surgery. In recent years, light medical beauty has been favored by people because of its simplicity, safety and youthfulness. This method uses injections to inject biological materials or synthetic materials with good biocompatibility into the dermis or subcutaneous layer, which can help people achieve skin tightening, wrinkle removal, facial micro-plastic surgery and facial rejuvenation. At the same time, it is recognized by the majority of medical beauty consumers because of its quick effect, small wound, short recovery period and high cost performance.
[0003] In recent years, a variety of filling materials containing microspheres have been approved for use, including poly-L-lactic acid, injectable poly-d,l-lactic acid, hydroxyapatite, polycaprolactone, etc. The application of microspheres can accelerate the formation of tissue cells and collagen in the filling area, improve skin aging, and prolong the filling effect. However, due to their hydrophobicity, microspheres are unstable in water, which makes it easy for the product to settle, stratify or agglomerate during production or storage. Therefore, the suspension and stability of microspheres in the product is an issue that needs to be optimized.
[0004] Agarose is a natural polysaccharide extracted from red seaweed, a linear polymer, and the raw material is soluble in hot water, and its aqueous solution can form gel at low temperatures. Agarose hydrogel has good biocompatibility, good degradation and absorption in vivo, and can be absorbed and metabolized by macrophage phagocytosis and pentose metabolic pathways, and the raw material is pure natural, non-toxic, and will not produce foreign body reaction or immune system reaction. Compared with other gels, agarose hydrogel has no hydrophilicity, and the injection effect is what you see is what you get. A small amount of injection can show obvious filling effect, and it is relatively stable in vivo, and the shaping effect is lasting, and it will not cause swelling, steaming, allergy, rejection and other problems, and is a more excellent injection filling material. It is recorded in CN116672498A that the water-agarose system can enhance the suspension stability of microspheres.
[0005] The disadvantage of agarose hydrogel as a medical injection material is that it is difficult to sterilize. Existing sterilization methods include dry heat sterilization, moist heat (steam) sterilization, chemical reagent sterilization, irradiation sterilization, filtration sterilization, etc.
[0006] Agarose hydrogel is not resistant to high temperatures. After heating, the gel easily turns back into a solution, and after cooling, it solidifies into a whole piece of gel, which cannot be taken out of the container and is even more difficult to inject through a syringe. In addition, the temperature during the heating and sterilization of the gel exceeds 100°C, and the hydroxyapatite microspheres that can be suspended at low temperatures will also precipitate. Some microspheres, such as polycaprolactone, will also melt and merge, making it difficult to resuspend in the packaging container, resulting in needle blockage. Therefore, it is difficult to use the usual wet heat and dry heat sterilization methods for agarose hydrogels containing microspheres. As a material for injection into the body, in order to prevent residues, reagents such as acetaldehyde and ethylene oxide cannot be used for sterilization. When using irradiation sterilization, agarose hydrogels will lose water (water seeps out of the gel), accompanied by a reduction in volume, and uncontrollable changes in physical properties such as viscoelasticity. Therefore, there is currently no method for large-scale production of agarose hydrogels containing microspheres with stable quality. Summary of the invention
[0007] Therefore, the technical problem to be solved by the present invention is to overcome the defect that agarose hydrogel in the prior art is difficult to sterilize. The inventor unexpectedly found in the experiment that agarose hydrogel material with a certain amount of cellulose and / or cellulose derivatives added does not lose water during irradiation sterilization, and the physical properties, especially viscoelasticity, hardly change after irradiation. At the same time, the gel can prevent the microspheres from agglomerating or settling during the solidification process, and can suspend the microspheres. The reverse replication process also promotes the microspheres to be evenly dispersed in the hydrogel, thereby providing a radiation-resistant agarose hydrogel material.
[0008] The invention provides an agarose composite hydrogel material containing microspheres. The polymer framework in the hydrogel material comprises agarose, cellulose and / or cellulose derivatives, the content of the agarose is 0.2%-8%wt of the hydrogel, the content of the cellulose and / or cellulose derivatives is 0.5%-15%wt of the hydrogel, and the hydrogel material further contains microspheres, and the content of the microspheres is 3%-40%wt of the hydrogel.
[0009] Preferably, the content of agarose in the hydrogel material is 1%-4%wt, the content of cellulose and / or cellulose derivatives is 2%-10%wt, and the content of microspheres is 5%-30%.
[0010] As an example, the weight of agarose in the hydrogel material is 0.2%, 1%, 2%, 2.5%, 3%, 3.5%, 4%, 6.5%, 8% of the weight of the gel; the weight of cellulose and / or cellulose derivatives is 0.5%, 2.5%, 3%, 4.5%, 6%, 7.5%, 12%, 15% of the weight of the gel; the weight of microspheres is 3%, 5%, 8%, 10%, 12%, 15%, 20%, 25%, 32%, 40% of the weight of the gel.
[0011] Preferably, the microspheres are selected from one or more of hydroxyapatite (HAP), poly L-lactic acid (PLLA), poly D-lactic acid (PDLA), poly racemic lactic acid (PDLLA), polyvinyl alcohol (PVA), polycaprolactone (PCL), polydioxanone (PDO), and polytrimethylene carbonate (P-TMC).
[0012] Preferably, the derivative group of the cellulose derivative contains a hydrophilic group, and the cellulose derivative is water-soluble, with a solubility of not less than 0.5 g in water at 37° C. The solubility of the present invention has a common meaning, that is, the mass of a substance that can be dissolved in 100 g of water.
[0013] As a further preference, the hydrophilic group is selected from one or more of -OH, -NH2, -COOH, -SO2H, -SO3H, -CHO, -CO-, -PO3H or pharmaceutically acceptable salts thereof.
[0014] As an example, the cellulose derivative is selected from one or more of carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, aminocellulose and their sodium salts, calcium salts, potassium salts, ammonium salts, sulfates, hydrochlorides, phosphates, hydrogen phosphates, dihydrogen phosphates, acetates, citrates, malates, methanesulfonates, benzenesulfonates, toluenesulfonates, amino acid salts and nicotinates.
[0015] The hydrogel material may also contain 0-5%wt of hyaluronic acid and / or hyaluronic acid derivatives, wherein the hyaluronic acid and its derivatives are hyaluronic acid, modified hyaluronic acid, cross-linked hyaluronic acid, or pharmaceutically acceptable salts thereof, and as an example, sodium hyaluronate, which is easily available on the market, may be used. Exemplary hyaluronic acid and / or hyaluronic acid derivatives may contain 0, 1%wt, 2%wt, 3%wt, 4%wt, or 5%wt.
[0016] Preferably, the hydrogel material has viscoelasticity, and Tanδ is between 0.01-0.4 at a frequency of 1 Hz.
[0017] The present invention further provides an injection for dermal layer and / or subcutaneous tissue injection, comprising the hydrogel material of the present invention.
[0018] Preferably, the gel of the injection is particles, and the particle size range D50 of the particles is less than 800 μm.
[0019] The present invention further provides a method for preparing the injection, comprising the following steps:
[0020] (1) Dissolving and dispersing: dissolving agarose and cellulose and / or cellulose derivatives in water, maintaining the temperature at 50° C. to 55° C. after dissolution, dispersing the microspheres in the resulting solution, and cooling to form a hydrogel;
[0021] (2) Granulation, filling, and sterilization.
[0022] During the dissolving step, hyaluronic acid and / or hyaluronic acid derivatives may be added to prepare a hydrogel containing hyaluronic acid and / or hyaluronic acid derivatives.
[0023] Since agarose has a high solubility in hot water and is easy to form a gel at low temperatures, it is easy to prepare a hydrogel by making the dissolution temperature higher than the temperature after cooling. In order to save time, hot water at, for example, 90-100°C can be used. The amount of each substance added can be simply calculated based on the desired gel composition. There is no special requirement for the order of addition. They can be added together or in any order. However, it can be understood by those skilled in the art that some types of microspheres have poor heat resistance and need to be cooled to a temperature they can tolerate before adding, and dispersed evenly by strong stirring.
[0024] Granulation is the process of converting hydrogel into particles by physical crushing. The particle size range D50 of the gel after granulation is less than 800 μm.
[0025] The granulated hydrogel particles have a certain fluidity under pressure and can be filled into various containers by conventional equipment (such as equipment for producing hyaluronic acid injections) and pushed through a needle (see the attached manual). Figure 1 and Figure 2 ), an exemplary container may be a vial, bag or syringe for injection.
[0026] When sterilizing, irradiation sterilization is used. You can refer to the standard "GB18280.2-2015 Sterilization Radiation of Medical and Healthcare Products Part 2: Establishing Sterilization Dose" and use gamma rays or beta rays for sterilization.
[0027] The present invention further provides the use of the hydrogel material or the injection in any of the following: (1) filling and increasing tissue volume, (2) correcting structural defects, and (3) improving skin condition. The structural defects include asymmetry, contour deformity, volume loss, and other defects that affect the appearance of the structure.
[0028] "wt" in the present invention means weight ratio. As an example, 2%wt means that 100g of hydrogel contains 2g of the substance. "Solution" in the present invention means a uniform liquid phase with fluidity, not a solid. With the increase in the amount of agarose and cellulose derivatives added, a more viscous liquid may be obtained, but as long as it still has fluidity, it still belongs to the category of "solution". "Gel" in the present invention means a gel solid that can still maintain its shape after leaving the container. It should be pointed out that although the granulated injection product has a certain fluidity under pressure, each of its particles can still maintain its shape after leaving the container, so it still belongs to the "gel" in the present invention. "Water" in the hydrogel in the present invention can be water for injection, or a solution containing small molecules dissolved in sodium chloride solution, glucose solution, phosphate buffer, etc. According to the injection site and specific use, those skilled in the art can change the osmotic pressure within a reasonable range (e.g., 0-1000mOsm / kg) to make it lower, equal to or higher than the osmotic pressure of human plasma. Various small molecules dissolved in water, including soluble salts and glucose added to adjust osmotic pressure, buffer substances added to adjust pH, water-soluble vitamins added to provide nutrition, local anesthetics added to relieve pain, etc., do not affect the formation of hydrogels within a reasonable dosage range, and basically do not affect the amount of water loss during radiation, and are irrelevant to the technical problems solved by the present invention. The concept corresponding to water and small molecules is "polymer framework". The presence of polymers such as agarose is the reason why hydrogels can be formed at room temperature. The polymers connected into a network structure with a molecular weight of not less than 1000 contained in the hydrogel are collectively referred to as "polymer framework". It is easy for those skilled in the art to understand that although various microspheres are also polymers, they are not connected to each other into a network and do not contribute to the formation of hydrogels, so they do not belong to polymer frameworks. The meaning of "injection" in the present invention is for injection into humans or animals, and does not mean that the defined product can be directly injected without further processing. The hydrogel intermediate product in the production process of injections also belongs to the category defined by "injection". The "not chemically cross-linked" mentioned in the present invention means that cross-linking is not performed intentionally by adding chemical cross-linking agents. The small dose of radiation used in irradiation sterilization may destroy the chemical bonds of the polymer and induce a trace amount of cross-linking reaction. At this time, the product should still be considered as "not chemically cross-linked".
[0029] The technical solution of the present invention has the following advantages:
[0030] 1. The agarose hydrogel material provided by the present invention can withstand irradiation sterilization, loses little or no water during irradiation, and the physical properties of the gel, especially the viscoelasticity, do not change significantly, thereby facilitating the production of products with stable quality at a lower cost.
[0031] 2. Using terminal irradiation sterilization can ensure product sterility and enhance safety.
[0032] 3. Compared with aseptic production process, terminal irradiation sterilization method can significantly reduce production costs.
[0033] 4. Cellulose substances can be metabolized quickly in the body and are safe and non-toxic.
[0034] 5. The microspheres have good biocompatibility, are non-toxic and non-irritating, are easy to combine with adjacent bone tissue, have a good filling effect, and have a slow metabolism. After the metabolism of agarose and cellulose, they can continue to stimulate collagen production and exert a long-lasting effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 It is the hydrogel injection product of Example 1 of the present invention;
[0037] Figure 2 is a photograph of the hydrogel product of Example 1 of the present invention passing through a needle;
[0038] Figure 3 This is a photo of the product after irradiation of Comparative Example 5 of the present invention (the right side is an enlarged view);
[0039] Figure 4 This is a photo of rabbit skin after injection of the product of Example 9;
[0040] Figure 5 This is a photo of rabbit skin 5 months after injection of the product of Example 9. DETAILED DESCRIPTION
[0041] Example 1.
[0042] Preparation of agarose composite hydrogels.
[0043] Agarose, sodium carboxymethyl cellulose and hydroxyapatite (HAP) were weighed, dissolved and dispersed in water for injection to obtain a solution containing 0.2% wt agarose, 2.5% wt sodium carboxymethyl cellulose and 3% wt hydroxyapatite (HAP) suspended therein, and the solution was allowed to stand and cool to room temperature to obtain a hydrogel.
[0044] The cooled hydrogel is crushed and filled into a pre-filled syringe, and then irradiated for sterilization (15 kGy, unless otherwise specified, this condition is used for subsequent irradiation). Figure 1The pushing effect is shown in Figure 2 shown.
[0045] After the gel was squeezed out and centrifuged (centrifugation conditions: 2000 rpm, 3 min), no water loss was found.
[0046] Example 2.
[0047] Agarose, sodium carboxymethylcellulose and poly-L-lactic acid (PLLA) were weighed, dissolved and dispersed in water for injection to obtain a solution containing 1% wt agarose, 4.5% wt sodium carboxymethylcellulose and 25% wt poly-L-lactic acid (PLLA) suspended therein, and the solution was allowed to stand and cool to room temperature to obtain a hydrogel.
[0048] The cooled hydrogel was crushed, filled into a pre-filled syringe, and sterilized by irradiation. The Tanδ of the product was measured to be 0.0912 at 1 Hz before irradiation and 0.0904 at 1 Hz after irradiation.
[0049] Example 3.
[0050] Agarose, hydroxyethyl cellulose and poly (d-lactic acid) (PDLA) were weighed, dissolved and dispersed in water for injection to obtain a solution containing 2.5% wt agarose, 6% wt hydroxyethyl cellulose and 40% wt poly (d-lactic acid) (PDLA) suspended therein, and the solution was allowed to stand and cool to room temperature to obtain a hydrogel.
[0051] The cooled hydrogel was crushed, filled into a pre-filled syringe, and sterilized by irradiation. The Tanδ of the product was measured to be 0.0869 at 1 Hz before irradiation and 0.0876 at 1 Hz after irradiation.
[0052] Example 4.
[0053] Agarose, hydroxyethyl cellulose, polyracemic lactic acid (PDLLA) and phosphate were weighed, dissolved and dispersed in water for injection to obtain a solution containing 4% wt agarose, 15% wt hydroxyethyl cellulose and 32% wt polyracemic lactic acid (PDLLA) suspended therein, the pH of the solution being about 6.7, and the solution was allowed to stand and cool to room temperature to obtain a hydrogel.
[0054] The cooled hydrogel is broken up, filled into pre-filled syringes, and sterilized by irradiation.
[0055] Example 5.
[0056] Agarose, hydroxypropyl cellulose, polyvinyl alcohol (PVA), 1%wt glucose, 0.01%wt aspartic acid, 0.03%wt glycine and 0.01%wt threonine were weighed and dissolved and dispersed in water for injection to obtain a solution containing 6.5%wt agarose, 12%wt hydroxypropyl cellulose and 5%wt polyvinyl alcohol (PVA) suspended therein, and the solution was allowed to stand and cool to room temperature to obtain a hydrogel.
[0057] The cooled hydrogel is broken up, filled into pre-filled syringes, and sterilized by irradiation.
[0058] Example 6.
[0059] Agarose, hydroxypropyl methylcellulose and polycaprolactone (PCL) were weighed, dissolved and dispersed in water for injection to obtain a solution containing 8% wt of agarose, 7.5% wt of hydroxypropyl methylcellulose and 3% wt of polycaprolactone (PCL) suspended therein, and the solution was allowed to stand and cool to room temperature to obtain a hydrogel.
[0060] The cooled hydrogel is broken up, filled into pre-filled syringes, and sterilized by irradiation.
[0061] Example 7.
[0062] Agarose, sodium carboxymethyl cellulose and hydroxyapatite (HAP) were weighed, dissolved and dispersed in water for injection to obtain a solution containing 3% wt agarose, 2.5% wt sodium carboxymethyl cellulose and 10% wt hydroxyapatite (HAP) suspended therein, and the solution was allowed to stand and cool to room temperature to obtain a hydrogel.
[0063] The cooled hydrogel is broken up, filled into pre-filled syringes, and sterilized by irradiation.
[0064] Example 8.
[0065] Agarose, sodium carboxymethyl cellulose and hydroxyapatite (HAP) were weighed, dissolved and dispersed in water for injection to obtain a solution containing 3.5% wt of agarose, 0.5% wt of sodium carboxymethyl cellulose and 12% wt of hydroxyapatite (HAP) suspended therein, and the solution was allowed to stand and cool to room temperature to obtain a hydrogel.
[0066] The cooled hydrogel was crushed, filled into a pre-filled syringe, and sterilized by irradiation. The Tanδ of the product was measured to be 0.1031 at 1 Hz before irradiation and 0.1024 at 1 Hz after irradiation.
[0067] Example 9.
[0068] Agarose, sodium carboxymethylcellulose, hydroxyapatite (HAP) and sodium hyaluronate were weighed, dissolved and dispersed in water for injection to obtain a solution containing 2%wt agarose, 3%wt sodium carboxymethylcellulose, 1%wt sodium hyaluronate and 20%wt hydroxyapatite (HAP) suspended therein, and the solution was allowed to stand and cool to room temperature to obtain a hydrogel.
[0069] The cooled hydrogel was crushed, filled into a pre-filled syringe, and sterilized by irradiation. The Tanδ of the product was measured to be 0.0892 at 1 Hz before irradiation and 0.0895 at 1 Hz after irradiation.
[0070] Example 10.
[0071] Agarose, sodium carboxymethylcellulose, polydioxanone (PDO) and sodium hyaluronate were weighed, dissolved and dispersed in water for injection to obtain a solution containing 2% wt of agarose, 2.5% wt of sodium carboxymethylcellulose, 3.5% wt of sodium hyaluronate and 15% wt of polydioxanone (PDO) suspended therein, and the solution was allowed to stand and cool to room temperature to obtain a hydrogel.
[0072] The cooled hydrogel is broken up, filled into pre-filled syringes, and sterilized by irradiation.
[0073] Example 11.
[0074] Agarose, sodium carboxymethylcellulose, polytrimethylene carbonate (P-TMC) and sodium hyaluronate were weighed, dissolved and dispersed in water for injection to obtain a solution containing 2%wt agarose, 2.5%wt sodium carboxymethylcellulose, 5%wt sodium hyaluronate and 8%wt polytrimethylene carbonate (P-TMC) suspended therein, and the solution was allowed to stand and cool to room temperature to obtain a hydrogel.
[0075] The cooled hydrogel is broken up, filled into pre-filled syringes, and sterilized by irradiation.
[0076] Comparative example 1.
[0077] Agarose and hydroxyapatite (HAP) were weighed, dissolved and dispersed in water for injection to obtain a solution containing 3% wt of agarose and 10% wt of hydroxyapatite (HAP) suspended therein, and the solution was cooled to room temperature to obtain a hydrogel.
[0078] The cooled hydrogel was broken into pieces.
[0079] During the granulation process, the gel lost water, and the water was removed by centrifugation. The water loss during the granulation process was 35% wt.
[0080] The gel obtained by centrifugation was filled and irradiated, and after irradiation, centrifuged and weighed. It was measured that the hydrogel lost 26%wt of water after irradiation. The Tanδ of the product was 0.6254 at 1Hz before irradiation; and 0.6335 at 1Hz after irradiation.
[0081] Comparative example 2.
[0082] Agarose and polycaprolactone (PCL) were weighed, dissolved and dispersed in water for injection to obtain a solution containing 8% wt of agarose and 3% wt of polycaprolactone (PCL) suspended therein, and the solution was cooled to room temperature after dissolution to obtain a hydrogel. The cooled hydrogel was crushed.
[0083] During the granulation process, the gel loses water and is centrifuged to remove water. The water loss during the granulation process is about 31%wt. The gel obtained by centrifugation is filled and irradiated. After irradiation, it is centrifuged and weighed. The sample also loses water, about 25.4%wt. The Tanδ of the product before irradiation at 1Hz is measured to be 0.6131; after irradiation, the Tanδ at 1Hz is 0.6281.
[0084] Comparative example 3.
[0085] Weigh sodium carboxymethylcellulose and hydroxyapatite (HAP) and dissolve and disperse them in water for injection to obtain a solution containing 2.5%wt sodium carboxymethylcellulose and 10%wt hydroxyapatite (HAP) suspended therein, and cool to room temperature to obtain a viscous liquid. The product is not formed and is not a hydrogel.
[0086] Comparative example 4.
[0087] Weigh sodium carboxymethylcellulose and poly-L-lactic acid (PLLA) and dissolve and disperse them in water for injection to obtain a solution containing 4.5%wt sodium carboxymethylcellulose and 25%wt poly-L-lactic acid (PLLA) suspended therein, and cool to room temperature to obtain a viscous liquid. The product is not formed and is not a hydrogel.
[0088] Comparative example 5.
[0089] The hydrogel was prepared by referring to Example 8, except that the sodium carboxymethylcellulose was replaced with 0.5% wt sodium hyaluronate (molecular weight 1340 KDa).
[0090] No water loss was observed during the granulation process. After filling and irradiation, the obtained hydrogel product was centrifuged and weighed. The sample lost water by about 24.2% wt. The Tanδ of the product before irradiation at 1 Hz was 0.5978; after irradiation, the Tanδ at 1 Hz was 0.6024. The photo of the product after irradiation is shown in the figure below. Figure 3 As shown, Figure 3 Obvious gel dehydration can be seen in Figure 1 There is a clear difference between the uniform gel in the medium.
[0091] Comparative Example 6.
[0092] The hydrogel was prepared with reference to Comparative Example 5, and the amount of sodium hyaluronate (molecular weight 1340 KDa) was increased to 2.5% wt.
[0093] No water loss was observed during the granulation process. After filling and irradiation, the obtained hydrogel product was centrifuged and weighed, and the sample lost water, which was about 24.8%wt.
[0094] Comparative Example 7.
[0095] The hydrogel was prepared with reference to Comparative Example 6, and the medium-molecular sodium hyaluronate was replaced with 2.5% wt of small-molecular sodium hyaluronate (molecular weight 340 KDa).
[0096] No water loss was observed during the granulation process. After filling and irradiation, the obtained hydrogel product was centrifuged and weighed, and the sample lost water by about 23.8%.
[0097] Comparative Example 8.
[0098] The hydrogel was prepared with reference to Comparative Example 5, except that the free sodium hyaluronate was replaced with 0.5% wt cross-linked sodium hyaluronate (prepared with 1,4-butanediol glycidyl ether (BDDE) as a cross-linking agent).
[0099] No water loss was observed during the granulation process. After filling and irradiation, the obtained hydrogel product was centrifuged and weighed, and the sample lost water, with a water loss of about 24.1%.
[0100] The product of Example 1-11 is in good condition before irradiation sterilization, cools and solidifies, is uniform and fine, has no granular feeling, and has viscoelasticity. After irradiation sterilization, the product is uniform and fine without precipitation. Taking Example 1 as an example ( Figure 1 ,2); The products of Comparative Examples 1 and 2 lost water to varying degrees during the granulation process and after irradiation. After water loss, the pushing force was uneven, and the needle was easily blocked or burst, and the product status did not meet the expected value; the products of Comparative Examples 3 and 4 were viscous and not coagulated, and were not hydrogels, so they were directly filled and sterilized; No water loss was observed during the granulation process of Comparative Examples 5, 6, 7 and 8, and the samples were uniform and delicate without a granular feel, but they all lost water to varying degrees after irradiation.
[0101] In order to more intuitively show the technical effect of the technical solution of the present invention, the component contents and properties of Examples 1-11 of the present invention and Comparative Examples 1-8 are listed in a table. The content in the table is in %wt, the particle size D50 is in μm, and the irradiation water loss means (the weight of water separated by centrifugation after irradiation) / (the weight of gel before irradiation)×100%.
[0102] Table 1 Example products (content unit is %wt).
[0103]
[0104]
[0105] Table 2 Comparative Example products (content unit is %wt).
[0106]
[0107]
[0108] Animal experiments.
[0109] Experimental method: Each tube is filled with 1 mL, a 27G needle is used, and 0.2 mL / point is injected subcutaneously into rabbits, for a total of 3 points.
[0110] Experimental results: The product (Examples 1-11) was injected subcutaneously without needle blocking, and the bulge was round and smooth. Taking the product of Example 9 injected subcutaneously into rabbits as an example, after injection, it can be observed that the bulge is round and firm ( Figure 4 is an enlarged picture); after 5 months, the bulge was round and normal ( Figure 5 (enlarged image), the bulge is slightly softer than when it was just injected. After 12 months, the bulge becomes flat, and the skin becomes thicker when lightly pressed. It proves that the product of the present invention can be used for subcutaneous injection filling, and can be decomposed and metabolized in the body after a reasonable period of time.
[0111] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. An agarose composite hydrogel material containing microspheres, characterized in that: The polymer framework in the hydrogel material includes agarose, cellulose and / or cellulose derivatives, the content of agarose is 0.2%-8%wt of the hydrogel, the content of cellulose and / or cellulose derivatives is 0.5%-15%wt of the hydrogel, and the hydrogel material also contains microspheres, and the content of the microspheres is 3%-40%wt of the hydrogel.
2. The hydrogel material according to claim 1, characterized in that The content of agarose in the hydrogel material is 1%-4%wt of the hydrogel, the content of cellulose and / or cellulose derivatives is 2%-10%wt of the hydrogel; the content of microspheres is 5%-30%wt of the hydrogel; and the hydrogel material also contains 0-5%wt of hyaluronic acid and / or hyaluronic acid derivatives of the hydrogel.
3. The hydrogel material according to claim 1 or 2, characterized in that: The microspheres are selected from one or more of hydroxyapatite (HAP), poly L-lactic acid (PLLA), poly D-lactic acid (PDLA), poly racemic lactic acid (PDLLA), polyvinyl alcohol (PVA), polycaprolactone (PCL), polydioxanone (PDO), and polytrimethylene carbonate (P-TMC).
4. The hydrogel material according to claim 3, characterized in that The average particle size of the microspheres is 1-100 μm, preferably 10-50 μm.
5. The hydrogel material according to claim 1 or 2, characterized in that: The derivatization group of the cellulose derivative contains a hydrophilic group, and the cellulose derivative is water-soluble, with a solubility of not less than 0.5 g in water at 37°C.
6. The hydrogel material according to claim 5, wherein the hydrophilic group is selected from one or more of -OH, -NH2, -COOH, -SO2H, -SO3H, -CHO, -CO-, -PO3H or pharmaceutically acceptable salts thereof.
7. The hydrogel material according to claim 5, characterized in that: The cellulose derivative is selected from carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, aminocellulose, and one or more of their sodium salts, calcium salts, potassium salts, ammonium salts, sulfates, hydrochlorides, phosphates, hydrogen phosphates, dihydrogen phosphates, acetates, citrates, malates, methanesulfonates, benzenesulfonates, toluenesulfonates, amino acid salts, and nicotinates.
8. The hydrogel material according to claim 1, characterized in that: The hydrogel has viscoelasticity, and Tanδ is between 0.01 and 0.4 at a frequency of 1 Hz.
9. An injection for injection into the dermis and / or subcutaneous tissue, characterized in that: Containing the hydrogel material according to any one of claims 1 to 8.
10. The injection according to claim 9, characterized in that: The gel of the injection is particles, and the particle size range D50 of the particles is less than 800 μm.
11. A method for preparing the injection according to any one of claims 9 to 10, characterized in that: The following steps are involved: (1) Dissolving and dispersing: dissolving agarose, cellulose and / or cellulose derivatives in water, maintaining the temperature at 50°C-55°C after dissolution, dispersing the microspheres in the resulting solution, and cooling to form a hydrogel; (2) Granulation, filling, and sterilization.
12. The method according to claim 11, characterized in that During granulation, the particle size D50 was controlled to be less than 800 μm, and irradiation was used for sterilization.
Citation Information
Patent Citations
Composite material for injection and application thereof
CN116672498A
Cited By
Polylactic acid / agarose microsphere-containing gel filling agent for injection and preparation method of polylactic acid / agarose microsphere-containing gel filling agent
CN121422300A
